Waste Bank Loose Part Sebagai Alat Edukasi Pembelajaran Steam Yang Aman Dan Ramah Lingkungan Di Paud Aisyiyah Al Amin Surakarta - Dina Pertiwi Ajie; Sari Pitria Ayu; Rizky Hanadya Tri Kusuma; Safira Meida Putri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In this pandemic transition era as a teacher we are required to overcome learning loss when children learn from home. Therefore, Loose Part media in STEAM learning is very helpful for children so that their developmental aspects can be achieved according to their age (Nurjanah, 2020). Loose Part media, which has many varieties around a safe and environmentally friendly environment for AUD, is the right medium today to achieve 6 aspects of child development (Kusuma dkk, 2022). Therefore, the existence of "Waste Bank Loosepart" at PAUD Aisyiyah Al Amin Surakarta really helps the availability of stock of goods in the school. Indirectly, we invite children, parents, teachers and the surrounding community to protect the environment to avoid piles of waste that can be recycled by saving in the birdhouse box. With the existence of "Wasten Bank Loospart" we indirectly realize an environmentally friendly school in the future. And realizing the golden generation of the Indonesian nation who cares about waste and a healthy environment.